The The Efficacy of using Wattpad to Advance Students' Writing Skills - Lilla - (STKIP PGRI SIDOARJO, 2023)
The purpose of the study is to assess the effectiveness of implementation Wattpad as a media on students writing skill at Tenth graders of SMKN 1 Pungging. This study applied Quasi Experimental with one-group pretest and posttest design. The participants of the study were 36 students. The data was served by numerical and tested by statistical formula t-test. The data was aimed by writing test score for both pre-test and post-test. The test was scored by two scorers using the same instrument. The results of this study show that the mean score of students has increased from 69.958 to 82.466 or 0,152% after the implementation of Wattpad as media in teaching and learning writing. It merely concludes that the implementation of Wattpad is effective to enhance students’ writing skills. Moreover, the value of the t-test is 11.211 while the value of t-table significance degree of 0.05 is 1.630. It indicates that t-test is higher than t-table consequently the null hypothesis is rejected and the alternative hypothesis is accepted. Based on the consideration, it concludes that Wattpad most significantly suggestion an effective media of improving teaching to enhance student’s writing skill.